Atrocities on scheduled castes - Saksena, H. S. (New Delhi : Serials Publications, 2010)
Study conducted in Budaun, Ghaziabad, Gonda, Gorakhpur and Hardoi districts of Uttar Pradesh, India.
Keywords: Dalits; Dalits; Atrocities